Impact of infrastructure on socio-economic development in rural areas: Evidence from the state of Haryana, India - Sharma, Ajai Pal and Kumar, Ajay (Indian Journal of Public Administration)
With a background to enhance the individual$1 (Bs capability and providing opportunities to rural community, rural development is unavoidable. Taking this idea of socio-economic enhancement at rural level, this paper examines the impact of rural infrastructure on the socio-economic development (SED) of rural people. Different dimensions related to rural infrastructure and SED are extracted in this paper using factor analysis. Regression analysis is employed using dimensions of rural infrastructure as independent variables and SED as dependent variables. Creation of water facilities as part of rural infrastructure was found to be the core dimension impacting the socio-economic life of the rural people followed by infrastructure maintenance and management of resources. Performance evaluation of panchayats, as a part of rural governance and execution of rural developmental activities, reveals that North Haryana leads on most of the parameters as compared to other parts of Haryana.- Reproduced s
Keywords: Rural development, Physical infrastructure, Socio-economic development, Rural community